Standards Used by a Clinical and Scientific Endometriosis Center for the Diagnosis and Therapy of Patients with Endometriosis - Burghaus, Stefanie; Hildebrandt, Thomas; Fahlbusch, Christine; Heusinger, Katharina; Antoniadis, Sophia; Lermann, Johannes; Hackl, Janina; Häberle, Lothar; Renner, Stefan P.; Fasching, Peter; Beckmann, Matthias; Blum, Simon (Geburtshilfe und Frauenheilkunde, 2019)
Endometriosis is one of the most common benign gynecological diseases. The extremely heterogeneous complex of symptoms complicates the diagnosis and treatment of this disease. In most patients, there is a latency period of several years between the first occurrence of symptoms and the definitive diagnosis. This paper aims (1) to evaluate standards for the diagnosis and treatment of patients with (symptoms suspicious for) endometriosis in terms of feasibility, and (2) to assess the potential use of data collected by a certified clinical and scientific endometriosis center to answer scientific questions. Standards for outpatient consultations were developed for a special endometriosis outpatient clinic. Between January 2014 and December 2017, a total of 1715 outpatients with a suspicion of endometriosis presented to this special endometriosis outpatient clinic; the diagnosis and treatment of patients was carried out in accordance with the developed standards. Data of this patient cohort obtained from patient records created during outpatient consultations and from a questionnaire recorded in an Oracle-based database was analyzed. The patient cohort was also compared with another patient cohort who had attended different outpatient clinics and had been diagnosed intraoperatively with endometriosis. 41.8% of patients examined during special outpatient consultations had surgery for suspicion or recurrence of endometriosis. Endometriosis was confirmed in 81.5% of cases. Pain symptoms were the main indication for surgery in 70.1% of cases compared to 45.1% of cases in the comparison group. The structured approach used in the special endometriosis outpatient clinic is a key aspect of the care provided by the certified clinical and scientific endometriosis center. It ensures that patients are diagnosed and treated in accordance with guideline recommendations, that diagnosis and treatment comply with certification requirements, and that the collected data can be used to answer scientific questions.
CRIS-Team Scopus Importer:2019-06-04
Keywords: diagnostic; endometriosis; lower abdominal pain; sterility